2014
DOI: 10.2971/jeos.2014.14018
|View full text |Cite
|
Sign up to set email alerts
|

Absorbance properties of gold coated fiber Bragg grating sensor for aqueous ethanol

Abstract: Optical Fiber Bragg Grating (FBG) is commonly deployed as a wavelength selective filter in telecommunication as well as to detect physical changes such as pressure, temperature and strain in sensing applications. This paper presents an investigation of FBG as a chemical sensor towards ethanol in aqueous solution. Telecommunication standard single mode FBGs were coated with different thicknesses of thin gold films via sputtering deposition method. The combination of Bragg gratings and gold film enhances the eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In return, these changes cause a corresponding change to the absorbance spectrum of the tapered fiber sensor. This is similar with the other reported work on fiber optic based Ethanol sensors [20,26].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In return, these changes cause a corresponding change to the absorbance spectrum of the tapered fiber sensor. This is similar with the other reported work on fiber optic based Ethanol sensors [20,26].…”
Section: Resultssupporting
confidence: 93%
“…Ethanol is a commonly utilized chemical in various industries such as medical, food processing, beverages and even as a replacement fuel in automotives [19,20]. Ethanol has a high volatility and flammability that can be dangerous for humans and living organisms, thus making the sensing of Ethanol crucial and important [21].…”
Section: Introductionmentioning
confidence: 99%
“…In a tapered fiber, a higher fraction of evanescent wave field passes inside the cladding, which is sensitive to the physical environment of its’ surroundings [ 19 , 29 ]. The interaction between the CNT on the tapered fiber tip and different concentrations of ethanol [ 30 ] molecules transforms the optical properties of the CNT film, resulting in the response of the developed sensors towards ethanol.…”
Section: Resultsmentioning
confidence: 99%
“…FBG was coated with different film thicknesses of gold by sputtering deposition technique and using it as a chemical sensor for ethanol in aqueous solution. It was found that the 50 nm gold film enhances the evanescent wave on the optical fiber surface and increases its sensitivity to detect ethanol with different concentrations [7].…”
Section: Introductionmentioning
confidence: 99%